Penanganan Sampah Skala Kawasan Di Fasilitas Unit Pengolah Sampah Dan Bank Sampah Di Kota Depok - Mochammad Chaerul; Dhia Atikah Aliyyu (EnviroScienteae, 2020)
Law No. 18 of 2008 on Waste Management prioritizes waste handling nearer the generator by considering economical value remained. In Depok City, waste handling at the community level has been performed at the Waste Treatment Unit (WTU) and waste bank. WTU focuses on organic waste treatment, while waste bank for inorganic waste recycling. The paper aims to identify waste generation and to evaluate the operational activity of the facilities. The sampling procedure proceeded for 8 days consecutively for 14 WTUs and 1 day for 7 waste banks applying stratified random sampling from a total of 30 WTUs and 428 waste banks operated in Depok City. Waste received daily were varied between 95,32-1.436,98 kg of organic waste at each WTU and 69,65-868,40 kg of inorganic waste at each waste bank. The variation of waste received was proportional to the number of inhabitants served and the character of the community surrounding the facility. The performance of the facilities could be improved including through promotion and financial support attained from the retribution. Waste handling at the community level could reduce the amount of waste transported to the Final Disposal Site (FDS) and reduce land required for FDS which becomes difficult to find especially in big cities in Indonesia.